2013
DOI: 10.1002/ccd.24700
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of orbital atherectomy for the treatment of calcified coronary lesions

Abstract: The ORBIT I trial suggests that the OAS may offer an effective method to change compliance of calcified coronary lesions to facilitate optimal stent placement in these difficult to treat patients. A larger trial is required to establish safety and overall effectiveness of the OAS in treating calcified coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 16 publications
2
75
0
2
Order By: Relevance
“…The Diamondback 360 Coronary OAS uses a differential sanding mechanism of action to remove plaque while potentially minimizing damage to the medial layer of the vessel. A drive shaft with an eccentrically mounted diamond-coated crown provides proximal and distal sanding to remove or reduce occlusive material and restore luminal patency (FIGURE 1C) [51]. The crown's orbital diameter expands radially via centrifugal force.…”
Section: Diamondback 360 Coronary Oasmentioning
confidence: 99%
See 2 more Smart Citations
“…The Diamondback 360 Coronary OAS uses a differential sanding mechanism of action to remove plaque while potentially minimizing damage to the medial layer of the vessel. A drive shaft with an eccentrically mounted diamond-coated crown provides proximal and distal sanding to remove or reduce occlusive material and restore luminal patency (FIGURE 1C) [51]. The crown's orbital diameter expands radially via centrifugal force.…”
Section: Diamondback 360 Coronary Oasmentioning
confidence: 99%
“…The first in man assessment of coronary orbital atherectomy to treat de novo calcified coronary lesions occurred during the ORBIT I clinical trial [51]. Fifty patients with de novo calcified coronary lesions were enrolled in this nonrandomized, multicenter trial in India.…”
Section: Clinical Studies Utilizing Orbital Atherectomy: Orbit I and Ormentioning
confidence: 99%
See 1 more Smart Citation
“…RA showed favourable results in treating HCCL in recent registries; however, there are no randomised trials concerning the use of RA in patients with severe TLC and AMI [20][21][22]. OA, a newcomer to coronary interventions, was first introduced in coronary arteries in 2013 in the ORBIT I trial [23]. Recent studies showed promising results of OA in hospital as well as in long-term follow-up [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…22 Fifty patients with de novo calcified coronary lesions were enrolled in this non-randomised, multi-centre trial in India.…”
Section: Clinical Evaluation For Coronary Orbital Atherectomy Systemmentioning
confidence: 99%